DETERMINING FACTORS IN CIVIL SERVICE CAREER DEVELOPMENT - Damima, Mohamad Juffry; Hamim, Udin (Universitas Negeri Gorontalo, 2022)
This research reviews about Career Development of Civil Servants (PNS) in Gorontalo Regency Government (Case Study at the Gorontalo Regency Personnel, Education and Training Agency). This research used qualitative descriptive approach, namely examining, analyzing and decrypting the data. The purpose of this study was to determine and analyze the factors that determine the career development of civil servants in the government of Gorontalo Regency. Research results: The factors that determine the career development of civil servants are, first, human resources include HR management, employee personnel consisting of formal education qualifications, civil servants competence, civil servant track record, civil servant behavior attitudes, integrity, discipline and loyalty; second, the commitment of superiors and teamwork that mutually support each other in the career development of civil servants; third, facilities, infrastructure, and budget; fourth, external factors can be in the form of political relations within the organization; fifth, regulations that support the career development of civil servants; sixth, the work performance of civil servants; and seventh, the motivation of civil servants.